Feeding Strategies and Nutritional Quality of Animal Products - Untea, Arabela Elena; Saracila, Mihaela; Vlaicu, Petru Alexandru (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The production of food enriched with bioactive compounds, through natural means, represents a concept desired by nutritionists, doctors and consumers. Animal products with high nutritional quality can be designed using innovative feeding strategies. Animals are known to be able to ''bio-convert'' health-promoting components from their diet into their eggs, milk or meat. The nutritional quality of animal products depends on genetic, physiological and environmental conditions, but also upon their diets. Lately, various feed additives have been shown to increase the nutritional quality of animal-origin food, which in turn promotes a healthy human diet. Some of them have proven effects on productive parameters or on the sensory attributes of animal products, or modify the nutrient composition of products. Nutritional evaluations of animal products and feeds are necessary for establishing the bioconversion yield of nutrients, from feeds to animal-origin food. This Special Issue focuses on, but is not limited to, the development of new feeding formulas thst lead to improved animal production or the enhanced nutritional profiles of conventional or ecological animal products. Studies presenting feed additives that have beneficial effects on the production and quality of animal products, as well as natural feeding solutions that are environmentally friendly, were also welcomed. The proposed Special Issue is addressed to specialists from the domains of animal nutrition, food quality, chemistry and biology.